Menanamkan Nilai Kasih Sayang Dan Toleransi Kurikulum Berbasis Cinta - Putri Zahara; Lu'luil Maknun (Jurnal Ilmu Pendidikan Guru Sekolah Dasar dan Usia Dini, 2026)
This study aims to instill the values of love and tolerance through a love-centered curriculum in schools, as an effort to create a humane and inclusive learning environment. The methodology used is a literature review by analyzing various studies, scientific articles, and educational documents related to the application of love and tolerance values in the learning process. These sources were systematically examined to identify concepts, strategies, and outcomes of implementing a love-based curriculum in different educational contexts. The results of this study indicate that the implementation of a love-based curriculum can enhance empathy, social care, and mutual respect among students. Previous research also emphasizes that the values of love and tolerance can be effectively taught through reflective, collaborative, and contextually appropriate learning methods. The conclusion of this study is that a love-based curriculum has great potential in building students' character filled with love and tolerance, making it highly relevant to be implemented at various educational levels. The research recommendations include the need for the development of learning models that emphasize affective aspects, formulation of policies that support the integration of love values in education, and further studies to test its implementation in diverse schools. The novelty of this research lies in the systematic integration of love and empathy into the formal curriculum, which is still rarely discussed in depth in Indonesian educational literature.